Shear behaviour and design of cold-formed ferritic stainless steel channels with circular web openings. (October 2021) - Yousefi, Amir M.; Samali, Bijan; Yu, Yang
Abstract: Web openings are commonly used for ease of maintenance, electrical and plumbing services. Placing openings in web, however, affects the shear strength of cold-formed stainless steel channels accordingly. This study aims to examine the effects of such web openings on the shear strength of cold-formed ferritic stainless steel channels without straps. The results of 21 shear tests on pair channels loaded at mid-length with span aspect ratio of 1.0 are presented. In terms of channels with web openings, the openings are placed either centred at mid-span or offset to the applied load. Quasi-static Finite Element (FE) model, considering material nonlinearity and initial geometric imperfection, is then developed and validated against experimental test results. In addition, The FE models are used for a parametric study to extend the test results for different channel thicknesses and circular web opening sizes. While no stainless steel standard provides shear strength reduction factors, and only the North American specification AISI S100:2016 and Australian/New Zealand Standard AS/NZS 4600:2018 for carbon steel members provide two equations for channels with centred openings, it is found that such equations are unreliable and un-conservative for ferritic stainless steel channels by as much as 20%. The results also demonstrated that the current equations in the literature for carbon steel channels are unreliable, and are either unconservative or too conservative to apply for ferritic stainless steel channels by up to 44%. Based on both experimental and numerical results, new reliable design equations in the form of shear strength reduction factors are proposed.